Psychosocial stress and its effects on health and memory as people age. - Lim, Tony Zhao Ming. (2012)
The effects of psychosocial stress have been a well-debated topic especially in the context of Singapore where stress levels are high. However, there are presently no published studies on the effects of psychosocial stress on health and memory in the Singapore context. The present study evaluated the effects of perceived psychosocial stress on perceived health and working memory in undergraduate and elderly samples in Singapore. In addition, age was examined as a moderator between the relationships of perceived stress, perceived health and working memory. 200 undergraduates and 99 elderly were administered the Perceived Stress Scale (PSS-10),the Health Status Questionnaire (HSQ-12) and a visuospatial working memory task. Regression analyses found that perceived stress was negatively related with perceived health but no significant relationship was found between perceived stress and working memory. Contrary to our hypotheses, age had no moderating effect on the relationships between perceived stress, perceived health and working memory. Limitations related to the use of self-report questionnaires and the nature of the visuospatial working memory task employed, are discussed. Findings from our study suggest future research to evaluate effects of psychosocial stress on health and on memory. Our results also have clinical implications that stress prevention programs should be developed to promote health in both clinical and healthy populations in Singapore.